Bernardin de Saint-Pierre and His Place on the Sun - Drozdek, Adam (Folia Philosophica, 2021)
In his Studies of nature (1784) and Harmonies of nature (1815) Saint-Pierre presented a panoramic view of nature as the work of omnipotent and benevolent God, whose providential care about His creation is everywhere visible. In this way, he wanted to call people to the life worthy of God, the life to be rewarded after death. The article discusses the nature of the universalist reward envisioned by Saint-Pierre in the light of his discussion of the spiritual nature of the human being. His view of this nature evolved and was not presented in entirely coherent fashion.